MEANING FIELD THEORY IN CELEBGRAM ENDORSEMENT PRODUCT CAPTIONS OF IKA PURPITASARI - Syafroni, Roni Nugraha (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Manufacturers of a product definitely want their products to be bought and used by the public. Everything is done by the marketing department of the product, including online marketing through social media. It is considered more effective and efficient. In Indonesia, the development of the online world continues to grow rapidly until now. Many online social media are used by Indonesian people, one of which is Instagram. Instagram is one of the favorite social media, sometimes termed celebgram or celebrities instagram.  Celebrities are chosen by product manufacturers to boost sales of their products in society. Celebgram with a fairly large number of followers are considered capable of becoming an online marketing agent. In this study, the researcher analyzes the caption of the endorsement of photo product from a celebrity named Ika Purpitasari. When analyzing the captions, the researcher uses the field of meaning theory derives from the semantic discipline. The photo captions analyzed by the researcher are those that contain endorsement products in the field of womanhood, such as women's fashion, women's beauty, and women's accessories. The  research method is descriptive analysis using the data collection techniques of documentation. The results of this study show that the field of meaning theory can be used outside of spoken language, namely when analyzing the captions in the photos of the celebgram.